Factor analysis of world record holders in athletic decathlon - Pavlovic, R.; Idrizovic, K. (Sport Science - International Scientific Journal of Kinesiology, 2017)
All-around competition is the only competition in which it does not matter whether the athlete is the first, the second or the last in a discipline. What matters is the total number of points, and a rounder competes against his/her personal capabilities and standards. Athletic all-around competitions are a series of consecutive athletic competitions divided in two days. Success is calculated by the sum score of all disciplines that are pointed due to the international athletic tables. The research included ten (10) is currently the world's best decathlete of all time until 2016. Aim of research was to carry out a factor analysis of the athletic decathlon world record holder in order to define factors (latent dimensions) that would determine the type of decathlon, or the so participation technical or motor discipline overall. Applying factor analysis in a defined area is extracted with a total of three factors explained about 75% of the common variance of. The first factor has exhausted 35.24% (pole vault, high jump, discus throw, 400m) and a set of common variance is defined as a type of jumper-thrower-runner. The second factor has exhausted 22.21% (100m; 110m hurdle) analyzed set and is defined as runners (sprinters) type athletes. The third factor has exhausted about 17% (long jump, 1500m) and is defined by a type of jumper-runner.